On the importance of reformatory establishments for juvenile delinquents - Pim, William Harvey (Statistical and Social Inquiry Society of Ireland, 1854)
The treatment of the juvenile portion of the destitute and criminal classes appears to be one of the most pressing social questions of the day?one in which our national prosperity and individual welfare are both intimately concerned; and the object of this paper is to show that, notwithstanding acknowledged improvements in the discipline of many of our prisons of late years, our present system of making no distinction between juvenile and adult delinquents, and our mode of dealing with the former class, are great errors in our social policy; that it is not only cruel and unjust, but unwise and prejudicial to the welfare of the community, being utterly abortive, promoting the very evils we wish to guard against, and productive of an enormous expenditure; and that it is due not only to the unfortunate class referred to, but to the community at large, to take steps to remedy this evil, and thus to wipe away the stain which attaches to this country for having so long neglected a paramount duty.
Read February 20th 1854
Keywords: Juvenile criminals; Reformatories; 314.15